2020
DOI: 10.1186/s13071-020-04406-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the susceptibility status of Aedes aegypti (Diptera: Culicidae) populations to pyriproxyfen and malathion in a nation-wide monitoring of insecticide resistance performed in Brazil from 2017 to 2018

Abstract: Background Chemical mosquito control using malathion has been applied in Brazil since 1985. To obtain chemical control effectiveness, vector susceptibility insecticide monitoring is required. This study aimed to describe bioassay standardizations and determine the susceptibility profile of Ae. aegypti populations to malathion and pyriproxyfen, used on a national scale in Brazil between 2017 and 2018, and discuss the observed impacts in arbovirus control. Methods The diagnostic-doses (DD) of pyriproxyfen and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…One crucial factor is the constant pressure of selecting mosquito populations resistant to insecticides, reducing the number of substance options, or increasing the amount used significantly [ 13 , 14 , 15 ]. In the last decade, Brazil has initiated a new chapter, willing to evaluate new approaches to controlling the mosquito population using alternatives [ 16 , 17 ], such as genetically modified organisms for population suppression [ 18 , 19 ]; mosquito population replacement carrying a symbiont [ 20 , 21 , 22 ]; the use pyriproxyfen in dissemination stations increasing juvenile mortality [ 23 , 24 ]; and at last, the use of sterile males, as proposed in this study [ 16 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…One crucial factor is the constant pressure of selecting mosquito populations resistant to insecticides, reducing the number of substance options, or increasing the amount used significantly [ 13 , 14 , 15 ]. In the last decade, Brazil has initiated a new chapter, willing to evaluate new approaches to controlling the mosquito population using alternatives [ 16 , 17 ], such as genetically modified organisms for population suppression [ 18 , 19 ]; mosquito population replacement carrying a symbiont [ 20 , 21 , 22 ]; the use pyriproxyfen in dissemination stations increasing juvenile mortality [ 23 , 24 ]; and at last, the use of sterile males, as proposed in this study [ 16 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three years later, Ae. aegypti populations resistant to the larvicide PPF were detected in some cities in the same region [ 24 ], which is predicted to undermine the control of mosquito-borne arboviruses. However, some authors have suggested that IR may also impinge on mosquito control through alterations in vector traits, especially vector longevity, competence, and behavior [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti in public health throughout Brazil since 2014, largely attributable to insecticide resistance (IR) in Ae. aegypti to other insecticides, including pyrethroids and organophosphates [ 23 , 24 ]. The most studied mechanisms responsible for the evolution of resistance are increased activity of detoxifying enzymes and modification of the insecticide target site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes the importance of vector control activities to deliver an adequate dose of insecticide and that failure to do so could enhance the observed resistance. Surveillance for the development of resistance for pyriproxyfen is important as there have been reports of resistance elsewhere in the world [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%